Temperature dependence in fast-atom diffraction at surfaces. Issue 20 (12th May 2022) - Pan, Peng; Debiossac, Maxime; Roncin, Philippe
Abstract : We investigate the influence of the temperature in Fast Atom Diffraction at surfaces. The inelastic profiles broaden rapidly while the elastic one is constant but its intensity decreases with a Debye-Waller factor adapted to grazing incidences. Abstract : Grazing incidence fast atom diffraction at crystal surfaces (GIFAD or FAD) has demonstrated coherent diffraction both at effective energies close to one eV ( λ ⊥ ≈ 14 pm for He) and at elevated surface temperatures offering high topological resolution and real time monitoring of growth processes. This is explained by a favorable Debye-Waller factor specific to the multiple collision regime of grazing incidence. This paper presents the first extensive evaluation of the temperature behavior between 177 and 1017 K on a LiF surface. Similarly to diffraction at thermal energies (TEAS), an exponential attenuation of the elastic intensity is observed but, contrarily to TEAS, the maximum coherence is not directly reduced by the attraction forces that increase the effective impact energy. It is more influenced by the surface stiffness and appears very sensitive to surface defects.